Pemilihan Duta Pondok Pesantren Menggunakan Metode Moora dan Aras - Saifur Rohman Cholil; Yudi Cahyono; Annisa Bunga Aurelia; Liliek Triyono (Department of Science and Technology Ibrahimy University, 2024)
This research was carried out with the aim of developing a decision support system that is expected to be able to provide assistance and simplify the process of assessing and calculating grades and shorten the time used in awarding Pesantren Ambassadors. This system will use two decision support system methods, such as the MOORA and ARAS methods. The MOORA (Multi-Objective Optimization Based on Ratio Analysis) method uses complex mathematical calculations to solve a problem. ARAS (Additive Ratio Assessment) is an approach based on the intuitive principle that the available options should be relevant. The ARAS method has the greatest ratio to achieve the most effective solution by looking at each weight and comparing the value of each criterion for each choice. The user can determine which method he will use in determining a decision. The final result that will be displayed by the system is a battle that shows which Islamic Boarding School is selected based on the two methods.